Assessing acrylamide content in sterilized Californian-style black table olives using HPLC-MS-QQQ and a potentiometric electronic tongue. (July 2020) - Martín-Vertedor, Daniel; Rodrigues, Nuno; Marx, Ítala M.G.; Dias, Luís G.; Veloso, Ana C.A.; Pereira, José Alberto; Peres, António M.
Abstract: The study aimed to evaluate the effects of olive cultivar (cvs. Manzanilla Cacereña and Hojiblanca ) and the sterilization intensity/time-period (F0 of 10–25 min at 121 ± 3 °C) on the formation of acrylamide in table olives and brine. Olive cultivar and thermal sterilization had a significant impact on the amount of acrylamide produced (varying from 228 ± 94 to 286 ± 110 and 336 ± 126 to 373 ± 159 ng g −1, for table olives and brine, respectively, determined by HPLC-MS-QQQ). Moreover, for both cultivars, linear positive relationships (0.931 ≤  R 2  ≤ 0.994) were found between the acrylamide concentration in olives and respective brine solutions, allowing to foresee a non-destructive indirect methodology for quantifying acrylamide in table olives. Finally, a potentiometric E-tongue was used to quantify acrylamide in both matrices. The lipid sensor membranes comprised on the sensor device showed potentiometric semi-logarithmic responses (0.962 ≤  R 2  ≤ 0.999) towards the acrylamide concentration for aqueous standard solutions, permitting the establishment of accurate multiple linear predictive models for the quantification of acrylamide in olives and brine solutions (repeated K -fold-CV: 0.97 ± 0.03 ≤  R 2  ≤ 0.99 ± 0.01; 12 ± 8 ≤ RMSE ≤ 28 ± 14 ng g −1 ) for both olive cultivars. E-tongue could be used as non-destructive indirect detection method of acrylamide, based on the brine solution evaluation, and so, a complementary analytical tool to the conventional chromatographic analysis. Graphical abstract: Image 1 Highlights: Olive cultivar influenced acrylamide synthesis in Californian-style black olives. Higher sterilization intensity/time-period increased acrylamide formation. Lipid sensor membranes showed satisfactory sensitivities towards acrylamide. E-tongue satisfactorily predicted acrylamide content in olives and brine solutions. E-tongue could be a complementary technique of HPLC-MS-QQQ for acrylamide detection.